A DFT study on optoelectronic properties of near-infrared In0.53Ga0.47As (001), (011) and (111) surfaces. (January 2021) - Fang, Qianglong; Shen, Yang; Liu, Zesen; Yang, Xiaodong; Zhang, Shuqin; Chen, Liang; Duan, Lingze; Xu, Shiqing
Abstract: The III-V In x Ga1- x As photocathodes have important application prospects in the fields of marine submarine exploration, marine communication, and undersea imaging. Different semiconductor surfaces show different atomic arrangements, leading to different properties. In this paper, the optoelectronic properties of three representative In0.53 Ga0.47 As surfaces have been studied and analyzed at the atomic levels by using the first-principles calculation method. Results show that the (001), (011) and (111) In0.53 Ga0.47 As surfaces are all chemically stable, and the lowest work function is obtained at (001) surface. The band diagram shows that the conduction bands of the three surfaces are all shifted down to the Fermi level. At the same time, the valence bands on the (001) and (111) surfaces move up, crossing the Fermi level, indicating the enhancement of metallic property. The narrowing of the conduction band leads to the weakening of electron locality. Among the three representative surfaces, the average absorption coefficient and reflectance of In0.53 Ga0.47 As (001) surface are decreased most significantly, reflecting higher photoelectrons emitting performance. Highlights: The photons are most likely to escape into the vacuum from the In0.53 Ga0.47 As (001) surface. The conduction bands of all three surfaces move downward, leading to the weakening of electron locality. The (001) In0.53 Ga0.47 As surface owns the strongest photo-emitting performance.